Enhancing Vocabulary Growth: A Comprehensive Study on Collaborative Game-Based Learning and Digital Integration - Sitohang, Claudya Septriana; Simanjuntak, Debora Chaterin (TELL - US JOURNAL, 2025)
This study explores the impact of collaborative game-based learning (GBL) and digital integration on vocabulary acquisition among English as a Foreign Language (EFL) learners. It investigates how interactive digital games, coupled with collaborative activities, enhance students' vocabulary retention and usage. Data was collected through qualitative data collection via online interviews on Google Meet and Zoom with 12 participants, the research reveals that students benefit from the social aspect of game-based learning, where collaboration with peers promotes active vocabulary use and real-time feedback. The study reveals that increased student engagement and motivation play a central role in enhancing vocabulary acquisition. Participants shared that the interactive and competitive nature of game-based learning (GBL) actively encouraged them to engage in vocabulary practice, making learning more enjoyable and dynamic. The findings highlight how game-based learning facilitates vocabulary acquisition through increased engagement and motivation. Collaborative and interactive learning fosters cognitive development and long-term retention.The real-time feedback provided by GBL helped students retain and apply new vocabulary over time. The collaborative aspect of GBL also emerged as a key factor in vocabulary learning, with students benefiting from peer interaction and shared knowledge in game-based environments. This collaboration fostered deeper understanding and allowed students to use vocabulary in meaningful contexts. Furthermore, personalized learning through digital tools was highly appreciated by participants, as adaptive features of digital platforms enabled them to learn at their own pace and tailor their learning experience to their individual needs, reinforcing vocabulary mastery. Overall, the study suggests that integrating GBL and digital tools not only aids vocabulary acquisition but also creates a more engaging, interactive, and personalized learning experience. These findings highlight the potential of incorporating these strategies into language instruction to strengthen vocabulary learning, provide real-world application opportunities, and advance overall language proficiency.